Polymorphism of the LCT gene regulatory region in Turkicspeaking populations of the Altay-Sayan region (southern Siberia) - I. V. Pilipenko; M. S. Pristyazhnyuk; V. F. Kobzev; M. I. Voevoda; A. S. Pilipenko (Вавиловский журнал генетики и селекции)
Retention of lactase activity in adulthood (lactase persistence) is one of the most important adaptive traits for human populations that consume fresh milk from domestic animals. At a molecular-genetic level, lactase persistence is determined by the presence of specific alleles of polymorphic sites in cis-regulatory elements of the LCT gene located on chromosome 2q21. Ascertainment of the molecular-genetic causes of lactase persistence has made this trait one of the most convenient for studying mechanisms of human population adaptation to environmental conditions. But the populations of many regions remain insufficiently investigated in relation to the genetic variability of the LCT loci. This paper presents the results of polymorphism analysis of loci, including the enhancer element for the LCT gene and its flanking regions, in two Turkic-speaking populations from southern Siberia, Altaian Kazakhs and Khakasses. It was found that the “European” allele LCT-13910T is the most characteristic of the Turkic-speaking populations from Altai-Sayan regions among all the polymorphic variants associated with lactase persistence. The expansion of the “European” allele LCT-13910T to the gene pool of the populations in southern Siberia could be related to migration waves of ancient herders form western Eurasia during the Bronze Age (in III – II millennium BC). A decrease of the LCT-13910T allele frequency and the total frequency of its carriers in the Turkic-speaking populations of southern Siberia in comparison with the majority of European populations and the Kazakhs from southern Central Asia can be attributed to: (1) a significant influence on the Altai- Sayan population’s gene pool by Eastern Eurasian populations, for which the LCT-13910T allele is rare; (2) a lesser adaptive significance of lactase persistence for south Siberian populations, compared to the populations of Europe. Rare and unique SNPs in the locus under consideration that were found in the Altaian Kazakhs (LCT-13895G > C and LCT-13927C > G) and Khakasses (LCT-14011C > T) potentially play a role in regulation of LCT gene expression, because they are located within the enhancer, regulating activity of its promoter.